Developing Technology-Based Learning Media to Improve Students’ Listening Skills in Rural Area - Sufrianti Purnama; Sam Hermansyah; Maulina; Nurul Aisyah Arif (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
Listening comprehension continues to pose a significant challenge for vocational high school students in Indonesia, largely due to their limited exposure to authentic listening materials and the continued reliance on conventional, teacher-centred instructional practices. Addressing this issue, the present study aimed to develop and evaluate technology-based learning media designed to enhance students’ listening proficiency. This study employed a Research and Development (R&D) approach, adopting the ADDIE model, which encompasses five systematic stages: Analysis, Design, Development, Implementation, and Evaluation. The participants consisted of 20 tenth-grade students from a vocational high school in Southeast Sulawesi. Data were collected through expert validation questionnaires, student response questionnaires, as well as pre-test and post-test assessments to measure students’ listening performance. The findings revealed that the developed learning media achieved high levels of validity and practicality, as indicated by expert evaluations. Furthermore, the implementation of the media led to a notable improvement in students’ listening comprehension, reflected in the significant increase between pre-test and post-test mean scores. Students also demonstrated highly positive responses, particularly in terms of the media’s attractiveness, ease of use, and perceived usefulness in supporting their learning process. In conclusion, the technology-based learning media developed in this study is both effective and feasible for enhancing listening comprehension among vocational high school students. These findings offer valuable pedagogical implications for English teachers, particularly in promoting the integration of technology-enhanced learning tools in vocational education settings.